Effect of machining and heating parameters on distortion of AISI 52100 steel bearing rings. (7th October 2005) - Surm, H.; Kessler, O.; Hoffmann, F.; Mayr, P.
In this work, the influences of different heating parameters on distortion of bearing rings (bearing steel AISI 52100, EN 100Cr6) are examined. The rings were machined in two different ways, which led to significant differences in roundness and residual stress distribution after machining. The heating parameters (heating rate, austenitising temperature, and stacking arrangement) were combined in a 23 full factorial matrix. In addition, the influence of preheating and soaking was examined. The cooling rate was very slow in order to avoid additional distortion during the cooling process. Also, distortion after heating and slow cooling is compared to that after quench hardening. The distortion of the rings during austenitising and slow cooling, in terms of change in roundness and change in flatness, is mainly influenced by stacking arrangement. The heating rate has a significant effect on the change in flatness and also influences the change in roundness. In addition, interactions of heating rate and stacking arrangement influence the change in flatness.